The Benefits, Challenges and Critical Success Factors of Big Data in Project management - Choy, Lai Fun (2015)
In the information era today, the emerging of modern and digital economy has spurred an unprecedented growth of data usage and traffic across the world via our daily activities. This evolution of data sources had introduced the term “BIG DATA”